Geological and Geomorphic Assessment of Wadi Al-Battum, Al Jabal Al Akhdar, Libya - Alzubir Abousaif; Ahmed Abuharara; Almahdi Bousayf; Mohamed Atia (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Al Jabal Al Akhdar basin formed from an active continental on the African platform in the late Triassic period. It is a vast sedimentary region in northeast Libya with North East/South West trending mobile component in Northern Cyrenaica province. Al-Battum Valley is located along the east coast of Libya, in the Northeastern part of Al Jabal Al Akhdar, and far 8 km west of Sousa City. The valley is one of many valleys that trend deeply toward the Mediterranean Sea. It consists mainly of Dernah formation (Eocene) and Quaternary deposits. The objectives of this study were to determine the relationship between structural controls and geomorphic characteristics in the study area, as well as the impact of lithology on the morphology and distribution of various karst features. Methods. This study included GDEM (Global Digital Elevation Model), field trips, aerial images; topographic maps, geological maps, and laboratory work were used to compile the data and results reported. The morphometric analysis of the GDEM performed by a geographic information system environment through spatial analyst tool of ArcGIS to extracted hydrological information like drainage networks. Results. The valley enclosed between two sinistral strike slip faults that trend almost NWN-SES; and a dextral strike slip fault that trend nearly East-West on the southern part of the Al Battum valley. The dominant type of joints are systemic joints that are oriented almost NE and their density increases in the main valley. Dernah formation is divided into three units based on hardness, color, size, concentration of the fossils, thickness of units, and Dunham classification. Three different types of Karren have been identified in the study area, and their distribution is predominantly controlled by lithology and structural factors. Solution basins are usually rounded to the oval in plain view, and their sides tend to be vertical to gently inclined, while the bottom is smooth and flat. Caves are karstic topography that appear in the study area as horizontally extending holes in sediment. Cave formation aided by structural features that act as a conduit for solution and karst formation. These strike slip faults affect the drainage pattern of the valley; and systemic joints set reveal the orientations of the principal stresses. Conclusion. This valley’s drainage system is sub-parallel to the dendritic drainage pattern, indicating that the area has been influenced by strike-slip action. The movement within the structure developed zones of broken and crushed rock fragments of various sizes, making surface and subsurface water dissolving easier. Darnah Formation (Middle-Late Eocene) Tertiary strata show noticeable and remarkable diverse shapes and sizes of karst (karren, solution basins and caves).